Fatty acid profile as a tool to trace the origin of beef in pasture- and grain-fed young bulls of Retinta breed - Alberto Horcada; Adoración López; Oliva Polvillo; Rafael Pino; Dolores Cubiles-de-la-Vega; David Tejerina; Susana García-Torres (Spanish Journal of Agricultural Research, 2018)
This research explores the possibility of using the fatty acid profiles of intramuscular fat to authenticate the origin of Retinta breed meat according to different feeding regimes based on the combined use of concentrate and grass or forage (GP, grass pasture; MC, medium concentrate; HC, high concentrate). Young bulls from GP (n=30) were reared on grass pasture and supplement with concentrate in controlled feeders; MC (n=30) and HC (n=15) were reared in farm buildings using 40 and 80% concentrate of total dry matter from diet, respectively. The stepclass function in R was used to perform a stepwise linear discriminant analysis including thirty fatty acids from intramuscular fat. Two fatty acids, 9c18:1 and 22:5 n-3 were selected as discriminators of the meat origin. Meat from the GP and MC was characterized by higher 22:5 n-3 (p<0.05), while HC meat showed higher 9c18:1 (p<0.05). The use of 9c18:1 and 22:5 n-3 fatty acids from intramuscular fat resulted in a correct assignation of 100% of beef samples to each of the feeding regimes. Therefore, in addition to serving as an effective tool for discriminating between feeding regimes in the origin of the beef, the fatty acid profile of intramuscular fat could help companies to check the authenticity of the meat origin.